Particulate amino acid and carbohydrates and particulate organic carbon and nitrogen in suspended and sinking organic matter from METEOR cruise M156 - Quentin Devresse; Kevin W Becker; Anja Engel (PANGAEA, 2024)
We collected in situ marine snow aggregates with a Marine Snow Catcher (MSC). The MSC allows studying the composition of suspended and fast-sinking organic matter from intact in situ formed aggregates (Riley et al. 2012). After deployment, the MSC was left vertically on deck for three hours, seawater containing suspended organic matter was collected from the top part of the MSC and fast-sinking organic matter was picked manually from the MSC base. The MSC was deployed within the mixed layer depth in the oxygen minimum zone (~400 m depth). Duplicate samples for particulate organic carbon (POC) and organic nitrogen (PON) were filtered onto pre-combusted (450 ?C for 5 h) Whatman GF/F filters (25 mm, 0.7 μm) under low pressure (< 200 mbar). Filters were frozen at -20 °C and stored until analysis. Prior to analysis, filters were acid-fumed (37% HCl for 24 h) in order to remove inorganic carbon and dried at 40°C for 24 h. Subsequently, filters were wrapped in tin cups (8 exttimes8 exttimes15 mm), combusted and analyzed according to Sharp (1974) using an elemental analyzer (Euro EA). We determined high-molecular-weight (>1 kDa) particulate combined carbohydrates (pCCHO) based on Engel and Händel (2011) and particulate hydrolysable amino acids (pHAA) based on Lindroth and Mopper (1979) and Dittmar et al., (2009). The analysis of pCCHO detected 11 monomers: and the pHAA analysis classified 13 monomers. The calculations for the carbon and nitrogen contents of pCCHO and pHAA were based on carbon and nitrogen atoms contained in the identified monomers.